Clinical characteristics and outcome associated with pandemic (2009) H1N1 influenza infection in patients with hematologic malignancies: a retrospective cohort study. Issue 6 (1st June 2013) - Minnema, Brian J.; Husain, Shahid; Mazzulli, Tony; Hosseini-Mogaddam, Seyed Mohammedmehdi; Patel, Mehul; Brandwein, Joseph; Reece, Donna; Lipton, Jeffrey H.; Rotstein, Coleman
Abstract: Pandemic H1N1 (pH1N1) influenza has been associated with a worldwide outbreak of febrile respiratory illness. Although impaired immunity, such as that caused by hematologic malignancy, has been identified as a risk factor for severe infection with this virus, the course of this infection has not been adequately characterized in patients with underlying hematologic malignancy in comparison with immune competent controls. We report our experience with severe pH1N1 infection in patients with hematologic cancers and compare this group to non-immunosuppressed patients. Data were retrospectively collected on all patients admitted to our institution with confirmed pH1N1 infection. Clinical characteristics, treatments and outcomes were compared between patients with hematologic malignancies and non-immunocompromised controls. Fifteen patients with hematologic malignancy and 49 controls were identified. The control group had higher baseline rates of asthma ( p = 0.01) and smoking ( p = 0.05) at baseline. Clinical features of infection in the two groups were similar, except for a higher prevalence of abnormalities on chest imaging in the group with malignancy ( p = 0.05). No statistically significant difference in mortality was observed between the groups. Mean duration of hospitalization (22.1 days vs. 9.2 days, p = 0.04) and duration of antiviral treatment (9.9 days vs. 6.7 days, p < 0.05) were greater in the hematologic malignancy group. Hospitalized patients with hematologic malignancies with pH1N1 infection had greater durations of hospitalization and treatment than non-immunocompromised controls, possibly reflecting decreased clearance of the virus as a consequence of impaired immunity.